Efek Penggantian Jagung dengan Biji Alpukat yang Direndam Air Panas dalam Ransum terhadap Retensi Bahan Kering, Bahan Organik dan Protein Kasar pada Ayam Broiler - Nelwida, Nelwida (Fakultas Peternakan Universitas Jambi, 2009)
This study was aimed to evaluate the effects of substitution of corn with avocado seed in the hot water on retention of dry matter, organic matter and crude protein of broiler chicken. This experiment was carried out in Poultry Nutrition Laboratory and the Department of Non Ruminant Nutrition of the University of Jambi. This study used 100 2-days broiler chickens strains Platinum given the basal ration with the addition of avocado seed flour. Completely Randomizing Design was used in the research with five treatments and four replications. The treatment given was the level of flour replacement of corn withavocado seed in the feed of BA-0 (no avocado seed), BA-5 (5% of avocado seed flour without soaking), BAR-% ( 5% avocado seed flour soaked in hot water), BA-10 (10% avocado seed flour without soaking) and BAR-10 (10% avocado seed flour soaked in hot water). Observed variables were retentions of DryMatter (DM), Organic Matter (OM) and crude protein (CP). The results showed that replacement of corn with avocado seed flour had no significant effect (P> 0.05) on retention of Dry Matter, Organic Matter and Crude Protein. In conclusion, the replacement of maize with wheat seeds, soaked avocadoseed and without soaking in hot water can be done without affecting the retention of Dry Matter, Organic Matter and Crude Protein.